Dietary carbohydrate intake, insulin resistance and gastro‐oesophageal reflux disease: a pilot study in European‐ and African‐American obese women. Issue 9 (1st September 2016) - Pointer, S. D.; Rickstrew, J.; Slaughter, J. C.; Vaezi, M. F.; Silver, H. J.
Summary: Background: Although obesity rates are higher in African‐American than European‐American women, gastro‐oesophageal reflux disease (GERD) and its comorbidities are more prevalent in European‐American women. A common denominator for increased adiposity, and consequent insulin resistance, is excess dietary macronutrient intake – which may promote greater prevalence and severity of GERD in women. Aim: To investigate whether GERD is more robustly associated with dietary carbohydrate intake, particularly dietary simple carbohydrate intake, and insulin resistance in European‐American women. Methods: About 144 obese women were assessed at baseline and 16 weeks after consuming a high‐fat/low‐carbohydrate diet. GERD diagnosis and medication usage was confirmed in medical records with symptoms and medications assessed weekly. Results: About 33.3% ( N = 33) of European‐American and 20.0% ( N = 9) of African‐American women had GERD at baseline. Total carbohydrate ( r = 0.34, P < 0.001), sugars ( r = 0.30, P = 0.005), glycaemic load ( r = 0.34, P = 0.001) and HOMAIR ( r = 0.30, P = 0.004) were associated with GERD, but only in European‐American women. In response to high‐fat/low‐carbohydrate diet, reduced intake of sugars was associated with reduced insulin resistance. By the end of diet week 10, all GERD symptoms and medication usage had resolved in all women. Conclusions: GERD symptoms and medication usage was more prevalent in European‐American women, for whom the relationships between dietary carbohydrate intake, insulin resistance and GERD were most significant. Nevertheless, high‐fat/low‐carbohydrate diet benefited all women with regard to reducing GERD symptoms and frequency of medication use.